Relationships between the Advanced Nursing Process quality and nurses' and patient' characteristics: A cross‐sectional study - Claudia Leoni‐Scheiber; Hanna Mayer; Maria Müller‐Staub (Wiley, 2020)
Abstract Aim This study aimed to assess (a) nurses' knowledge and their attitude towards the Advanced Nursing Process-nursing assessment, diagnoses, interventions, outcomes, (b) the quality of the Advanced Nursing Process and (c) relationships with patient characteristics. Design A cross‐sectional, descriptive correlational study was performed. Methods Ninety‐two registered nurses and ninety nursing records of six hospital wards were included. In January 2016, a knowledge test, a self‐assessment tool for measuring nurses' attitude (PND) and the Quality of Diagnoses, Interventions and Outcomes Revised instrument (Q‐DIO R) were applied. The correlations between nurses' knowledge, attitude, patient characteristics, organizational factors and the Advanced Nursing Process quality were investigated. Results Nurses demonstrated low levels of knowledge, positive attitudes and an average Advanced Nursing Process quality. Accurate nursing diagnoses were strong and highly significantly related to effective nursing interventions and better nursing‐sensitive patient outcomes. A higher proportion of registered nurses was related to better nursing outcomes.